APPLICATION OF BIM IN MEDICAL BUILDING CONSTRUCTION PROJECTS: BARRIER FACTORS AND SOLUTION STRATEGIES: A CASE STUDY OF CHENGDU MEDICAL BUILDING CONSTRUCTION PROJECT - Jiahao Chen; Laemthong Laokhongthavorn (Operational Research in Engineering Sciences: Theory and Applications)
In recent years, the use of BIM software in clinical building tasks has been paid greater and extra attention. Taking Chengdu's scientific development mission as an example, this paper discusses the utility of BIM in scientific building projects and researches the impediment elements and answer strategies. This paper makes use of semi-structured interviews and literature evaluations to evaluate every influencing aspect earlier than by conducting quantitative research. After amassing facts via qualitative methods, an online questionnaire survey was once built in accordance with the interview consequences and previous lookup papers, and a number of factors blanketed in the online questionnaire had been comprehensively explained, and the software state of affairs and present issues of Building Information Modeling (BIM) in scientific development tasks have been summarized. The consequences of the lookup exhibit that the predominant boundaries to the positive adoption of BIM technological know-how in Medical Building Construction Projects (MBCPs) departments in Chengdu are multifaceted. First, issues from collaboration and verbal exchange stand out. These challenges are compounded with the aid of doubtful roles and obligations inside the mission team. This ambiguity now not solely hinders fantastic teamwork but also prevents BIM from seamlessly integrating with present workflows. Second, there are full-size boundaries to interoperability and compatibility problems between exclusive BIM software program applications. This incompatibility creates limitations to the clean alternate of records and data, leading to inefficiencies and plausible blunders in challenge execution. The large range of software programs used at one-of-a-kind degrees of MBCPs exacerbates this problem. Finally, the inherent complexity of BIM software programs and tools, coupled with the time-consuming and cumbersome BIM process, poses a big challenge. This complexity frequently leads to a reluctance amongst stakeholders to embody BIM technology. Given these findings, this study learns about the stage for future lookup and sensible interventions aimed at advertising wider acceptance and the tremendous use of BIM in the Medical Building Industry (MBI) and Construction Industry (CI).